Comparative Anatomical and Biometrical Studies on Liver of Bakerwali and Nondescript Goats of Union Territory of J&K - Sethi, Lovish (Indian Journal of Veterinary Anatomy, 2020)
The present study was conducted on liver of young, adult and senile Bakerwali and non-descript goats. The liver of both the breeds was almost rectangular. The colour was reddish brown. Liver of Bakerwali goat was darker in colour. Liver was divided into caudate and main lobe. The main lobe was further divided into dorsal, middle and ventral parts. Dorsal border presented caudate lobe. Medial border presented notch for oesophagus. Parietal surface was convex. Visceral surface presented impressions for omasum and reticulum. Liver was attached to surrounding structures by five ligaments. Different biometrical parameters were recorded in different age groups of Bakerwali and non-descript goats.